Lower Extremity Reconstruction with Vascularized Free-Tissue Transfer: 20 Years of Experience in the Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand - Akaranuchat, Nutthawut (Siriraj Medical Journal, 2021)
Objective: The reconstruction of extensive soft-tissue defects in the lower extremity still poses a great challenge to plastic and reconstructive surgeons. The ideal approach is to achieve a proper soft-tissue coverage with a well-vascularized flap, which results in a durable weight-bearing surface and permits normal joint motion. This study aims to retrospectively analyze the outcomes of lower-extremity reconstruction with vascularized free-tissue transfer performed at our plastic surgery division. Materials and Methods: A retrospective chart review was performed regarding 58 patients with defects in the lower extremity which were reconstructed with vascularized free-tissue transfers between 2000 and 2019. Forty-four of the patients were male, and 14 were female. The mean age was 44.4 years (range: 6-89 years). The most common indication for free-flap surgery was a secondary reconstruction after tumor eradication (23 cases, 39.7%), and 84.8% of the defects were exposed bare bones, tendons, or joints. Results: In our 58 reviewed cases, the foot was the most common area requiring reconstruction with a free flap (68.9%), and the mean defect size was 12.5 x 8.1 cm. The most commonly used free flap was the Anterolateral thigh free flap (39.7%), followed by the Gracilis free flap (29.3%), and the Superficial circumflex iliac artery-perforator free flap (10.4%). The recipient vessels most frequently used were posterior tibialis vessels (53.4%). The overall flap-survival rate was 75.9%, though there was an increased survival rate of up to 85.7% in the last five years of the period studied. The flap-salvage rate was 40.9%, and arterial thrombosis was the major cause of flap loss (50%). Factors associated with free-flap failure were re-exploration and free flap surgery after tumor or cancer eradication. The most common post-operative complication was flap-wound dehiscence (10.3%). Two patients received a flap correction due to bulkiness, and three had recurrence of ulceration. Conclusion: Microvascular free-tissue transfers for lower- extremity-defect reconstructions are reliable and valuable as a surgical technique. In over 20 years of experience in our division, we’ve had an overall flap-survival rate of 75.9%. Our flap of choice was the Anterolateral thigh free flap.